An In Vitro Study of The Spore Densities Effect of Trichoderma spp. as Biocontrol Agent for Fusarium Wilt in Cayenne Pepper (Capsicum sp.) - Tsania Taskia Nabila; Ika Afifah Nugraheni; Rais Sulistyo Widiyatmoko; Wiwit Probowati (International Journal of Health Science and Technology, 2021)
Root disease controlling has been a challenge in increasing plant productivity. The soil-borne pathogens become the main concern which mostly infects the root surface. One of the most common soil-borne pathogens is Fusarium oxysporum (Fo). Cayenne pepper (Capsicum sp.) is one of the most abundant commodities and contributes significantly to the economy. This plant is also susceptible to Fusarium wilt infection. The use of endophytic fungi as biocontrol agents is an alternative against soil-borne pathogens, one of which is Trichoderma spp. fungi. This study aims to determine the effectiveness of various spore densities of Trichoderma spp. against the pathogen Fo. The research was conducted through an in vitro study by antagonistic testing between spore suspensions of Trichoderma spp. (103, 105, and 107 spores/mL) with Fo. The results showed the density of 107 spores/mL gave the highest percentage of inhibition (54.59%) compared to spore density of 103 (35.27%) and 105 spores/mL (44.44%). The spore density of 107 spores/mL gave a significant difference in response to the density of other spores according to the BNT test at a significance level of 5% and was able to inhibit the growth of Fo more than 50%. The results of this study are expected to be a reference for the formulation of Trichoderma spp. which is ideal for controlling Fo pathogens in the fields.